Effect of school-based interactive nutrition promotion on knowledge and attitudes toward the free Nutritious Meal Program (MBG) among junior high school students in West Aceh - Maiza Duana; Amiruddin Amiruddin; Ambia Nurdin; Sri Maywati; Saprizal Saprizal (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
School-based nutrition promotion is essential for improving adolescents’ knowledge and attitudes toward healthy eating and government-supported nutrition programs. However, junior high school students have a limited understanding of and less favorable attitudes toward the Free Nutritious Meal Program (MBG). This study aimed to evaluate the effect of a six-week school-based interactive nutrition promotion intervention integrated into the MBG on students’ knowledge and attitudes in West Aceh, Indonesia. A quasi-experimental pretest–posttest design with a control group was conducted among 277 students in grades VII–IX at the State Junior High School 3 Meulaboh. Participants were selected using proportionate stratified random sampling and assigned to the intervention (n = 140) and control (n = 137) groups. The intervention group received structured interactive nutrition education sessions, whereas the control group received only MBG. Knowledge and attitudes were measured using validated questionnaires, before and after the intervention. Data were analyzed using the Wilcoxon signed-rank and Mann–Whitney U tests. The results showed significant improvements in knowledge and attitude scores in the intervention group compared to the control group (p < 0.001). Integrating interactive nutrition promotion into school meal programs effectively enhances students’ understanding and attitudes, supporting the educational value and sustainability of the MBG.